Meningkatkan Hasil Belajar Matematika Siswa melalui Pendekatan Komputasi dan Pendekatan Pemecahan Masalah Polya - Risa Chusniah; Ani Afifah (Delta-Phi: Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the improvement of students' mathematics learning outcomes through the application of the Computational Thinking approach and the Polya problem-solving approach. This study used a quasi-experimental method with a Non-Equivalent Control Group Design. The subjects were 28 students of class VIII A of SMP Negeri 4 Pasuruan as the experimental group and 23 students of class VIII B as the control group. The instruments used were pretest and posttest tests on the data centering material. Data analysis was carried out using the Wilcoxon Signed Rank test because most of the data were not normally distributed. The test results showed a significant improvement in both groups after treatment. However, the improvement achieved by students in the Computational Thinking group was higher than that of the Polya group. This proves that Computational Thinking is more effective in encouraging students to think systematically, analytically, and reflexively in solving mathematical problems.